Test de operaciones básicas para el aprendizaje de las matemáticas - Vicuña Peri, Luis A. (2000)
The purpose of the present study consists on offering to the psychological and pedagogic community a test that allows to evaluate the basic operations for the learning of the mathematics and in turn to plan the corrective strategies. He/she has taken into account the contributions of Jean Piaget in the concerning thing lo the development of the Cognitive integrated function by the logical thought and the organization of the reality. The test was proven with a sample of the 1008 students that you/they study the secondary level whose ages go from the 12 to the 17 ages with 11 months, of slate schools of Lima. For the Dependability the method of the halves was used, he/she was coefficients R of Spearman Brown 0,81 up to 0,94, being the indexes of reliability of 0,90 up to 0,97. He/she was also considered the dependability for the method of the internal consistency using the equation of Kuder-Richardson, finding coefficients of 0,86 up to 0,90. The Validity of construct validity, confirmed that indeed the students with high yield in the test, had a yield average in significantly more mathematics regarding the students of low yield in the test. In the Predictive validity that is correlating each subtest and the total score with the yield in the subject of mathematics was coefficients of 0,31 up to 0,60, For the Empiric Validity, with the analysis intertest correlation and total-test it was in all the cases very significant correlation coefficients, but in all case the coefficient is such that it indicates that a variable measures the same thing that the other one, maintaining its independence. By means of the Factorial Analysis it is assumed that the five factors are parts of an only factor, denominated basic operations for the mathematics what you confirmed by means of the test SCREE of Cattell and the program of Kaiser, as well as the Adjustment of Kindness and Index of Adaptation carried out with the program EQS. for what was demonstrated that the ideal pattern is similar to the theoretical pattern of a single factor.